The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.3727/096368917x694688
|View full text |Cite
|
Sign up to set email alerts
|

Cryopreservation of Hepatocyte Microbeads for Clinical Transplantation

Abstract: Intraperitoneal transplantation of hepatocyte microbeads is an attractive option for the management of acute liver failure. Encapsulation of hepatocytes in alginate microbeads supports their function and prevents immune attack of the cells. Establishment of banked cryopreserved hepatocyte microbeads is important for emergency use. The aim of this study was to develop an optimized protocol for cryopreservation of hepatocyte microbeads for clinical transplantation using modified freezing solutions. Four freezing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…45 The use of apoptosis inhibitors is also effective in improving thawed hepatocyte viability and function of alginate-encapsulated and cryopreserved hepatocyte microbeads. 46 The microenvironment in which cells are transplanted is a critical consideration in the success of cell therapy. Cells enter the liver via sinusoids where they integrate with the parenchyma.…”
Section: Overcoming the Challenges Of Cell Therapy For Liver Diseasementioning
confidence: 99%
“…45 The use of apoptosis inhibitors is also effective in improving thawed hepatocyte viability and function of alginate-encapsulated and cryopreserved hepatocyte microbeads. 46 The microenvironment in which cells are transplanted is a critical consideration in the success of cell therapy. Cells enter the liver via sinusoids where they integrate with the parenchyma.…”
Section: Overcoming the Challenges Of Cell Therapy For Liver Diseasementioning
confidence: 99%
“…2b). However, it was shown that even cryopreservation has a considerable effect on the viability and metabolic function of these cells due to cells being subjected to damaging conditions during both freezing and thawing steps [47][48][49][50]. To increase cryopreserved cell viability, Jitraruch et al developed an optimized protocol for cryopreservation of hepatocyte microbeads using modified freezing solutions [47].…”
Section: Pitfalls and Hurdles To Overcome In Liver Cell Therapiesmentioning
confidence: 99%
“…Moreover, allogenic hepatocyte transplantation should be still followed by an immunosuppressive therapy used for OLT [44,74,76]. To overcome these limitations, cells can be transplanted within a biodegradable scaffold, such as microcapsules and microbeads, to provide a microenvironment suitable for cell attachment and also protect cells from host's immune system [47,77]. The fact that hepatocytes are typically harvested from livers not suitable for transplantation makes quantity and quality of cells obtained highly variable [78].…”
Section: Pitfalls and Hurdles To Overcome In Liver Cell Therapiesmentioning
confidence: 99%
“…Those observations are insufficient to determine capsule stiffness and pore size, and assure the capsules without the antioxidants, their efficiency could be questioned [12]. On the other hand, anti-apoptotic factor effects in CPA solution were investigated with hepatocytes reducing apoptosis significantly in the first 24 hours after thawing [81]. In this regard, cell death and apoptosis behavior within microcapsules have not been carefully studied after cryopreservation.…”
Section: Expert Opinion and Future Directionsmentioning
confidence: 99%
“…The only method to preserve cell-based systems or products for long periods is with the use of low temperatures. Thus, the efforts to cryopreserve cell-based products made of natural polymers (e.g., agarose, hyaluronic acid, fibrin or collagen) or synthetic polymers (e.g., PEG) have linearly grown with its reflection in more publications in last decades[22,30,47,79,81]. Alginate has been one of the most often used polysaccharides to form cellularized bioscaffolds due to its potential as sustained drug delivery or cell delivery systems for the treatment of different diseases (e.g., diabetes, hepatic diseases, neurodegenerative or cancer among others)[82][83][84][85].…”
mentioning
confidence: 99%